(untitled) (Research, Society and Development, 2021)
Endometriosis is an inflammatory reaction caused by the presence of extrauterine endometrial tissue that affects women of reproductive age, and may be associated with the development of pathologies such as several types of ovarian cancer. The aim of this study was to find in the literature evidence that associates endometriosis with the development of ovarian cancers. For the selection of articles conducted in 6 methodological steps: preparation of the guiding question, establishment of inclusion and exclusion criteria of articles, exploratory reading of titles and abstracts of articles for pre-selection, full reading of articles, interpretation of results and synthesis followed by presentation of the results identified. Fourteen publications were found between the years 2010 and 2020, of which 4 (28.57%) were published in China, 4 (28.57%) in the United States, 3 (21.42%) in Spain, 2 (14.8%) in Japan, and 1 (7.14%) in Romania. Study types ranged from case report, observational, comparative, and randomized clinical trials. There was no prevalent uniformity of the results found. The studies analyzed in this paper showed no significant relationship between ovarian cancer and endometriosis, and further investigations are needed, but point to more efficient options for diagnosing ovarian tumors in their early stages, enabling a better prognosis.